Enhancement of P2X3 Receptor-Mediated Currents by Lysophosphatidic Acid in Rat Primary Sensory Neurons - Qiao, Wen-Long; Li, Qing; Hao, Jia-Wei; Wei, Shuang; Li, Xue-Mei; Liu, Ting-Ting; Qiu, Chun-Yu; Hu, Wang-Ping (Frontiers in Pharmacology, 2022)
Lysophosphatidic acid (LPA), a lipid metabolite, plays a role in both neuropathic and inflammatory pain through LPA1 receptors. P2X3 receptor has also been shown to participate in these pathological processes. However, it is still unclear whether there is a link between LPA signaling and P2X3 receptors in pain. Herein, we show that a functional interaction between them in rat dorsal root ganglia (DRG) neurons. Pre-application of LPA enhanced P2X3 receptor-mediated and α,β-methylene-ATP (α,β-meATP)-evoked inward currents in a concentration-dependent and voltage-independent manner. LPA shifted the concentration-response curve for α,β-meATP upwards, with an increase of 44.18 ± 8.74% in the maximal current response of P2X3 receptors to α,β-meATP in the presence of LPA. Enhancement of α,β-meATP-evoked currents by LPA was blocked by the LPA1 receptor antagonist Ki16198, but not by the LPA2 receptor antagonist H2L5185303. The LPA-induced potentiation was also prevented by intracellular application of either G- protein inhibitor or protein kinase C (PKC) inhibitor, but not by Rho inhibitor. Moreover, LPA increased the membrane excitability of DRG neurons, with a significant increase in the amplitude of the depolarization and the number of spikes induced by α,β-meATP in the presence of LPA. Finally, LPA exacerbated α,β-meATP- induced nociceptive behaviors in rats. These results suggested that LPA enhanced the functional activity of P2X3 receptors in rat primary sensory neurons through a mechanism that depends on the activation of the LPA1 receptor and its downstream PKC rather than Rho signaling pathway, indicating a novel peripheral mechanism underlying the sensitization of pain.